Effect of dietary folic acid additions on sow performance through two parities - R C Thaler; G L Allee; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1988)
A total of 153 gilts from three breeding groups were fed gestation/lactation diets supplemented with either 0, 1.5, or 6.0 g of folic acid/ton of complete feed for two consecutive parities. Serum folate levels were linearly increased by dietary additions of folic acid throughout gestation and lactation, but serum glucose and urea levels were unaffected by treatment. Stage of life cycle also had an effect on serum folate level. Generally, folate levels decreased from breeding to day 60 of gestation in parity 1 for all treatments, then increased through lactation. In parity 2, folate levels decreased up to day 90 of gestation, then increased through lactation. Number of pigs born alive, on day 14, and on day 21 were all quadratically increased by folic acid additions. Individual pig weights were similar on day 0 and day 14 of lactation, though less on day 21 for pigs from sows receiving 1.5 g/ton treatment. Total litter weights were quadratically increased on day 0 and day 14 by folic acid supplementation. Sow weight change and backfat thickness loss were unaffected by treatment during gestation, but quadratically decreased during lactation. Fewer sows receiving folic acid supplementation exhibited estrus by day 7 postweaning in parity 1; however, no differences were observed between treatments by day 14 nor were any observed by day 7 in parity 2. Also, conception rate was unaffected by folic acid additions. Based on these results, folic acid supplementation improves sow performance by increasing number of pigs born alive by 1 pig, and 1.5 g of folic acid/ton elicited the optimum response.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Folic acid; Sow; Gestation; Lactation